2013
DOI: 10.3382/ps.2012-02837
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Salmonella in skinless chicken breast fillets by lauric arginate surface application ,

Abstract: Lauric arginate (LAE) has been found to be effective against various foodborne pathogens. In this study, the antimicrobial efficacy of LAE against Salmonella and mesophilic organisms was evaluated in fresh, skinless, boneless, uncooked chicken breast fillets. The effect of LAE treatments on pH and color of breast fillets was also assessed. Chicken breast fillets were inoculated with a 4-strain Salmonella cocktail (Salmonella Enteritidis ATCC 4931, Salmonella Heidelberg ATCC 8326, Salmonella Kentucky ATCC 9263,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 21 publications
2
21
1
Order By: Relevance
“…Reductions in C. jejuni counts with carvacrol 18 and MAP were dose dependent and the lowest reduction in counts was observed on d 0. The 19 reductions observed were 0.5, 0.7, and 0.8 log CFU/g with 0.25, 0.5, and 1% carvacrol 20 treatments (in combination with MAP). On d 1 higher reductions of C. jejuni were obtained (1.0, 21 1.7, and 1.8 log CFU/g with 0.25, 0.5 and 1% carvacrol treatments, respectively in combination 22 with MAP as compared to aerobic positive control).…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…Reductions in C. jejuni counts with carvacrol 18 and MAP were dose dependent and the lowest reduction in counts was observed on d 0. The 19 reductions observed were 0.5, 0.7, and 0.8 log CFU/g with 0.25, 0.5, and 1% carvacrol 20 treatments (in combination with MAP). On d 1 higher reductions of C. jejuni were obtained (1.0, 21 1.7, and 1.8 log CFU/g with 0.25, 0.5 and 1% carvacrol treatments, respectively in combination 22 with MAP as compared to aerobic positive control).…”
mentioning
confidence: 83%
“…All carvacrol treatments exhibited concentration dependent reduction of19 Salmonella in combination with MAP. The Salmonella reductions obtained on d 0 with the 20 combination of carvacrol and MAP were lower (P ≤ 0.05) compared to all other sampling days.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…The application of 200 ppm of LAE significantly reduces Salmonella spp. on chicken breast fillets up to 1 log CFU/g during refrigerated storage up to 7 days (Sharma et al, 2013a). Benli et al (2011) reported that sequential spray application of 200 ppm of LAE followed by 30% acidic calcium sulfate reduced Salmonella on chicken carcasses by 2.2 log CFU/ml.…”
Section: Introductionmentioning
confidence: 99%